2016
DOI: 10.1080/10495398.2016.1168304
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Newly Discovered Polymorphisms of theCEBPDGENE LOCUS and Body Parameters in Sheep

Abstract: An understanding of what effects particular genes can have on body parameters in productive animals is particularly significant for the process of marker-assisted selection. The gene of transcriptional factor CCAAT/enhancer-binding protein delta (CEBPD gene) is involved in the process of growth in animals and is known to be a promising candidate for use as a genomic marker. The structure of the CEBPD gene locus was determined using NimbleGen sequencing technology (Roche, USA). The effect of polymorphisms, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As a result of the obtained associations, an important finding is that the CEBPD gene region located in the 31.5-32.5 Mb region on chromosome 9, which is known to be under selection, can serve as a significant marker gene in selection applications conducted in breeding studies focusing on fertility and lamb development characteristics in the Esme breed over the course of several years. As a matter of fact, Trukhachev et al (2016) found that polymorphisms in the CEBPD gene region were associated with body parameters in sheep. These polymorphisms were also suggested as markers for breeding programs aimed at improving meat production.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the obtained associations, an important finding is that the CEBPD gene region located in the 31.5-32.5 Mb region on chromosome 9, which is known to be under selection, can serve as a significant marker gene in selection applications conducted in breeding studies focusing on fertility and lamb development characteristics in the Esme breed over the course of several years. As a matter of fact, Trukhachev et al (2016) found that polymorphisms in the CEBPD gene region were associated with body parameters in sheep. These polymorphisms were also suggested as markers for breeding programs aimed at improving meat production.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of reports have appeared that noted the relationship between the different gene polymorphisms and the meat production of sheep bred in Russia (Gorlov et al 2016;Trukhachev et al 2016Trukhachev et al , 2017Gorlov et al 2018b). The purpose of these studies was to enhance the level and quality of meat production, as well as reduce the cost of feed per unit of production in Russian sheep breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we identified some genes that simultaneously influence multiple traits. For example, the CEBPD gene has been reported to affect both body parameters [48] and adipogenesis [49]. Watanabe et al [50] highlighted that pleiotropic genes are active in multiple tissues and participate in numerous biological functions within the organism.…”
Section: Identification Of Roh Islands Candidate Genes and Qtlmentioning
confidence: 99%